Analisa Tingkat Kepuasan Masyarakat Terhadap Kualitas Pelayanan CCTV Lalu Lintas Menggunakan Metode Naïve Bayes - Pandu Dharma Putra; Jemakmun Jemakmun (STMIK Budi Darma, 2023)
This study aims to determine the level of public satisfaction with the quality of traffic CCTV services at the Palembang City Police Station based on the results of a questionnaire containing Tangibles, Reliability, Responsiveness, Assurance, Emphaty. This research is a quantitative research. The subject of this study was the community of Palembang city which amounted to 300 people Data collection uses questionnaire questionnaires, while data analysis is processed and calculated in mining applications, namely rapidminers using the Naïve Bayes method. The results showed that out of 300 respondents, 73 were very satisfied, 139 satisfied, 34 neutral, 29 dissatisfied, and 25 very dissatisfied. While the most respondents based on gender attributes are men with a total of 166, age attributes are 20-30 with a total of 86, education attributes are high school with a total of 150, job attributes are private employees with a total of 140, vehicle attributes are motorcycles with a total of 150. And from the category is Satisfied with the number of 139.